Fracture of the mandible treatment in a child: a simplified technique - Christoph H. Houben; Lundy Campbell; Chuol Chiok Stephen Kuol (PAGEPress Publications, 2023)
After being hit by a motorcycle a seven-year old boy presented with a displaced fracture of the body of the right mandible [type III]. In the absence of orthodontic internal fixation or ligature wire equipment suture material was used to provide approximation and stabilisation of the fracture. The non-absorbable suture was fed through a cannula which was pierced through the bone on either side of the fracture. We present this simplified technique as a suitable alternative for the fixation of mandible fractures in settings with very limited resources.